Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian AC Panasonic - Fadia Afriyani; Reminta Lumban Batu (UNHI Press, 2022)
This study aims to determine the effect of product quality on purchasing decisions for AC Panasonic, to determine service quality on purchasing decisions for AC Panasonic. To find out and explain the effect of product quality and service quality on purchasing decisions. This study uses two independent variables, namely product quality (X1), service quality (X2), and one dependent variable, namely purchasing decisions (Y). The types of data used in this research are primary data and secondary data. This research method uses descriptive and verification methods with a quantitative approach. The sample used was 104 respondents. The data analysis technique used is multiple regression analysis with the help of the SPPSS 21 tool. The results of the study prove that product quality has a significant effect on purchasing decisions for Panasonic ACs, and service quality has a partially significant effect on purchasing decisions for Panasonic ACs. Product quality and service quality simultaneously have a simultaneous influence on purchasing decisions